Ozonolysis of α-amino-α/-hydroxymethyl-4-nitroacetophenone in the liquid phase - G. A. Galstyan (Zaporozhye State Medical University, 2017)
Recent studies have shown that the existing problems on levomycetin synthesis can be solved involving ozone as technologicaly undiluted oxidant. It is known that during the industrial synthesis of levomycetin, 50% of intermediate l-threo-1-(4-nitrophenyl)-2-amino-1,3-propanediol (I), namely l-(+)-threo-1-(4-nitrophenyl)-2-amino-1,3-propanediol (II) is a waste which is not used. Therefore, the current proposals are to return intermediate II in the synthesis of levomycetin. On the first stage of such method secondary alcohol group is oxidized to carbonyl one. Then ketones are succumbed to racemization and recovery with further use in synthesis. The purpose of this work is the study of l-(+)-threo-1-(4-nitrophenyl)-2-amino-1,3-propanediol oxidation with the use of ozone-air mixture to produce α-amino-α/-hydroxymethyl-4-nitroacetophenone. Materials and methods. As starting substances l-(+)-threo-1-(4-nitrophenyl)-2-amino-1,3-propanediol (hereafter "alcohol") were used. Its oxidation with the help of ozone-air mixture in acetic acid and in the presence of mineral acids at 20 °C lead to α-amino-α/-hydroxymethyl-4-nitroacetophenone (hereafter "ketone") creation. The identification of the synthesized compounds was performed by IR spectroscopy. The determination of ketone III and 4-nitrobenzoic acid was reproduced on photoelectrocolorimetre. Ozone was generated in laboratory in a quiet ozonizer discharge of high voltage from the purified dry air. The determination of the concentration of ozone in the ozone-air mixture was carried out by spectrophotometry. Results. The physical-chemical properties of the substance and its structure were confirmed by IR spectroscopy. We used the kinetic research methods. Studies have shown that the starting alcohol in acetic acid at 20 °C is oxidized with ozone indiscriminately, the main pro-oxidation products are ketone (35 %) and 4-nitrobenzoic acid (34.9 %). The selectivity of the oxidation is doubled (71.5 %) by oxidation in the presence of equimolar amounts of mineral acid (preferably hydrochloric acid). The content of 4-nitrobenzoic acid thus reduced to 2.5 %. Conclusions. The reactions of the alcohol II oxidation with the help of ozone mixture in acetic acid medium at 20 °C have been researched. It has been revealed that the oxidation selectivity by α-CH bond increases in the presence of mineral acids.